2014
DOI: 10.2337/db13-1842
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Heparanase Taken Up by Cardiomyocytes Regulates Lipoprotein Lipase Transfer to the Coronary Lumen After Diabetes

Abstract: After diabetes, the heart has a singular reliance on fatty acid (FA) for energy production, which is achieved by increased coronary lipoprotein lipase (LPL) that breaks down circulating triglycerides. Coronary LPL originates from cardiomyocytes, and to translocate to the vascular lumen, the enzyme requires liberation from myocyte surface heparan sulfate proteoglycans (HSPGs), an activity that needs to be sustained after chronic hyperglycemia. We investigated the mechanism by which endothelial cells (EC) and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…5,[7][8][9] Following its nuclear entry, Hep A also influences transcription by cleaving nuclear HSPG, mitigating the suppressive effect of heparan sulphate on histone acetyltransferase. [10][11][12][13][14] More recently, we established a novel role for Hep A in modulating cardiac metabolism during diabetes. 10,15 The above studies in cancer and diabetes fixated on the effects of Hep A , incorrectly assuming that only the HSPG-hydrolyzing ability of heparanase was of importance.…”
Section: In Cancer Biology Hepmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[7][8][9] Following its nuclear entry, Hep A also influences transcription by cleaving nuclear HSPG, mitigating the suppressive effect of heparan sulphate on histone acetyltransferase. [10][11][12][13][14] More recently, we established a novel role for Hep A in modulating cardiac metabolism during diabetes. 10,15 The above studies in cancer and diabetes fixated on the effects of Hep A , incorrectly assuming that only the HSPG-hydrolyzing ability of heparanase was of importance.…”
Section: In Cancer Biology Hepmentioning
confidence: 99%
“…[10][11][12][13][14] More recently, we established a novel role for Hep A in modulating cardiac metabolism during diabetes. 10,15 The above studies in cancer and diabetes fixated on the effects of Hep A , incorrectly assuming that only the HSPG-hydrolyzing ability of heparanase was of importance. Intriguingly, Hep L also has some remarkable properties, including its ability to activate signalling elements like Erk1/2, PI3K-AKT, RhoA, and Src, which in turn can contribute to changes in transcription.…”
Section: In Cancer Biology Hepmentioning
confidence: 99%
“…14 translational (?heparanase-mediated) mechanisms, with increased H-LPL in diabetes [22,23] as a consequence of the hyperglycemia [53].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…LPL is produced by cardiomyocytes, which need endothelial-derived heparanase for LPL production. In this issue, Wang et al (7) demonstrated that endothelial heparanase is taken up by the cardiomyocytes through caveolae and is converted to an active form in the lysosomal compartments of these cells. Endothelium-derived heparanase is instrumental for cleaving and releasing LPL from the heparan sulfate proteoglycans on the cardiomyocyte cell surface.…”
mentioning
confidence: 99%
“…The released VEGF may stimulate an autocrine signaling by signaling through VEGF receptors present on the cardiomyocyte cell surface, turning on the AMPK-p38 MAP kinase pathway and rearranging cytoskeleton to propagate the LPL vesicles from inside of cardiomyocyte to the outer membrane (12). Wang et al (7) showed that heparanase augments cellular transcriptional machinery through increased histone acetyl transferase (HAT) activity (Fig. 1).…”
mentioning
confidence: 99%